Exploring Reflective Practice-Based Learning Through Game-Based Design - Petersen, Anne Kristine; Riis, Marianne; Tretow-Fish, Tobias A.B. (Proceedings for the European Conference on Reflective Practice-based Learning 2025, 2025)
This study examines DidakTekQuest, a board game designed to enhance Continuing Professional Development (CPD) for in-service educators by integrating Game-Based Learning (GBL) with Reflective Practice-based Learning (RPL). Framed within a design-based research methodology, the paper analyses the game's intended design to explore how it can cultivate collaboration, dialogue and reflection to promote in-service educators’ understanding of digital technology in their teaching practices. Drawing on theoretical frameworks including the concept of double stimulation, the study demonstrates how game elements can stimulate agency, dialogue and pedagogical exploration. The results highlight the potential of game-based learning to stimulate reflective dialogue and critical thinking that enable educators to meaningfully incorporate digital tools into their teaching practices.